PENGARUH KOMPRES DINGIN TERHADAP INTENSITAS NYERI PADA BAYI SAAT IMUNSISASI CAMPAK DI WILAYAH KERJA PUSKESMAS TALAGA JAYA - Andi Akifa Sudirman; Muriyati Rokani; Atin Pateda (Universitas Muhammadiyah Gorontalo, 2019)
This research was conducted at Telaga Jaya health centre work area of gorontalo district. The objective was to identification the influence of before and after cold compresses used quasi eksperiment design on the influence of pain intensity in infants during measles immunization. The design used quasi eksperiment one group pretest-postets. The population were the mothers who have 9 months old infants. The samples are 15 respondents. Cold compresses applied 21 times in 3 weeks, the assessment was before and after treatment which used T-test Dependent test on pressure level 95% (????=0,05). The result obtained the enhancement influence before and after cold compresses on pain intensity in infants during measles immunization.